Analisis Konsep Rancangan Produk Kartu Saku P3K Berbasis QR Code untuk Meningkatkan Nilai Fungsional, Ergonomi, dan Estetika - Nabila Putri Aprilia Nur Cahyanti; Wardatul Elsa Bilbina; Putri Hajar Syalsabilah; Bertrand Okthaddeus; Vira Febrianti; Dafa Fadhilah Hilmi; Nashifa Maisun Nuhita; Ahmad Raziqi (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2025)
This study aims to develop a functional, ergonomic P3K pocket card design that meets user needs and is in line with the latest product design developments. This P3K pocket card is designed as a practical health education medium for emergency use. The methods used are a combination of structured literature studies and a qualitative descriptive approach. The research involved a comprehensive review of scientific publications focusing on product design, ergonomics, and health technology from 2020 to 2025. This review aims to integrate important findings regarding function, aesthetics, ergonomics, and value of use in formulating the design principles of the P3K pocket card. Ergonomic principles (ease of use) and aesthetics (visual appeal) are the main focus of the design. The results of the study show that the proposed P3K Pocket Card design is able to effectively integrate clinical functions (essential P3K information), modern design aesthetics, and ergonomics (ease of carrying and access). This design produces an educational medium that is not only practical and accessible, but also increases the potential for P3K knowledge transfer among the general public and non-medical personnel.